Strategi Mengurangi Masalah Keterlambatan Waktu Tiba dan Berangkat KM Umsini dan KM Dobonsolo di Pelabuhan Soekarno Hatta Makassar - Arif Fuddin Usman; St. Retno Ayuningtias; Andi Rustan; Febrian James; Mutmainna Rachman (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2024)
The purpose of this research is to determine strategies for addressing the delays in the arrival and departure times of KM Umsini and KM Dobonsolo owned by PT. Pelni (Persero) at the Port of Makassar based on SWOT analysis recommendations. The data processed includes qualitative data on estimated arrival times compared to the actual arrival times of the vessels, as well as estimated departure times compared to the actual departure times. The results show that the average delay in the arrival of KM Dobonsolo is 1 hour and 18 minutes, while the average delay in departure is 2 hours and 5 minutes. The average delay in the arrival of KM Umsini is 3 hours and 8 minutes, and the average delay in departure is 3 hours and 12 minutes. The strategies implemented to improve the factors affecting the punctuality of the vessels' arrival and departure times include the Embarkation/Debarkation Service Process, the Loading/Unloading Process, the Freshwater Bunkering Process, the Fuel Bunkering Process, and the delays in the IT system facilitated by Inapornet in handling Clearance Documents.